2022
DOI: 10.1177/13657127221088328
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion of evidence in times of mass surveillance. In search of a principled approach to exclusion of illegally obtained evidence in criminal cases in the European Union

Abstract: The article discusses the rationales for excluding illegally obtained evidence in criminal cases starting from two recent judgments of the European Court of Justice on mass data collection. The two decisions concern the exclusion of evidence obtained as a result of the retention of metadata in breach of EU law. According to the ECJ, exclusion may be justified by on the basis of the principle of effectiveness and the consequent need to protect the suspects’ rights (protective principle). Based on its analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
1
0
2
Order By: Relevance
“…120 The impact of this case law, however, is not entirely clear. 121 In a Belgian Sky ECC case, the Antwerp Court of Appeal acknowledged that the right to privacy had been violated, as some of the collected data were retained under a data retention law that had been annulled in the meantime. In light of the above-mentioned case law of CJEU, the court found that the reliability of the data was not at stake and that the defendants had had the opportunity to challenge the data.…”
Section: Privacy Violationsmentioning
confidence: 99%
“…120 The impact of this case law, however, is not entirely clear. 121 In a Belgian Sky ECC case, the Antwerp Court of Appeal acknowledged that the right to privacy had been violated, as some of the collected data were retained under a data retention law that had been annulled in the meantime. In light of the above-mentioned case law of CJEU, the court found that the reliability of the data was not at stake and that the defendants had had the opportunity to challenge the data.…”
Section: Privacy Violationsmentioning
confidence: 99%
“…Com o objetivo de identificar a lógica atinente ao artigo 69(7), a autora analisou a fundamentação para a exclusão de provas ilícitas em sistemas jurídicos nacionais e internacionais antes de concluir que a da integridade reveste a regra do Estatuto de Roma (Viebig, 2016, p. 123). Para não se restringir à revisão de uma única obra, a pesquisa se estendeu para textos referenciados no trabalho de Viebig (Safferling, 2001;Penney, 2003;Zappalà, 2003;Thake, 2005;Alamuddin, 2010;Slobogin, 2013) e outros estudos que trataram de lógicas de exclusão em variados sistemas jurídicos (Madden, 2014;Chau, 2016;Piragoff & Clarke, 2016;Roberts et al, 2016;Ho, 2019;Lin et al, 2019;Turner & Weigend, 2019;Heinze, 2020;Kremens & Jasinski, 2021;Kuczynska, 2021;Weigend, 2021;Panzavolta et al 2022), 3 a fim de compreender se haveria outras lógicas de exclusão que ainda não foram mencionadas nas decisões do artigo 69(7).…”
Section: Justificativas Para a Exclusão De Provas Ilícitasunclassified
“…15 Foram identificadas abordagens, por exemplo: i) que dividem a integridade enquanto conceito geral e a integridade sistêmica (Turner &Weigend, 2019); ii) que incorporam a ideia de aproximação/afastamento da Corte da violação na lógica da exclusão (Viebig, 2016); iii) que tratam da aproximação/afastamento como lógica conectada porém derivada (Madden, 2014); iv) que incluem a lógica do julgamento justo na fundamentação da integridade (Slogbogin, 2013;Roberts et al, 2016), e v) que incluem na integridade noções de afastamento, julgamento justo, proteção da rule of law, dissuasão e remediação (Heinze, 2020). 16 Panzavolta et al (2022) entendem que o balanceamento é um grande mérito da teoria da integridade, pois articula a tensão entre a busca pela verdade e a preservação dos direitos do acusado (p. 82). 17 Viebig (2016) Para além de questões gerais como a aplicação das questões de provas a todos os estágios do procedimento e a discricionaridade dos juízes (regra 63), as rpp definem apenas três questões procedimentais de prova, nos parágrafos da regra 64, estabelecendo que: i) qualquer questão de prova seja levantada assim que conhecido o fato sobre ela (parágrafo 1º); ii) as Câmaras Julgadoras devem fundamentar qualquer decisão relativa à admissibilidade das provas (parágrafo 2º), e iii) qualquer prova considerada inadmissível não seja utilizada pela Câmara na sua decisão (parágrafo 3º).…”
Section: Teoria Da Preservação Da Integridade Do Tribunalunclassified